Heterogeneous factors influence social cognition across diverse settings in brain health and age-related diseases - Fittipaldi, María Sol (2024)
Aging may diminish social cognition, which is crucial for interaction with others, and significant changesin this capacity can indicate pathological processes like dementia. However, the extent to which nonspecific factors explain variability in social cognition performance, especially among older adults and inglobal settings, remains unknown. A computational approach assessed combined heterogeneouscontributors to social cognition in a diverse sample of 1063 older adults from 9 countries. Support vectorregressions predicted the performance in emotion recognition, mentalizing, and a total social cognitionscore from a combination of disparate factors, including clinical diagnosis (healthy controls, subjectivecognitive complaints, mild cognitive impairment, Alzheimer’s disease, behavioral variant frontotemporaldementia), demographics (sex, age, education, and country income as a proxy of socioeconomic status),cognition (cognitive and executive functions), structural brain reserve, and in-scanner motion artifacts.Cognitive and executive functions and educational level consistently emerged among the top predictorsof social cognition across models. Such non-specific factors showed more substantial influence thandiagnosis (dementia or cognitive decline) and brain reserve. Notably, age did not make a significantcontribution when considering all predictors. While fMRI brain networks did not show predictive value,head movements significantly contributed to emotion recognition. Models explained between 28–44% ofthe variance in social cognition performance. Results challenge traditional interpretations of age-relateddecline, patient-control differences, and brain signatures of social cognition, emphasizing the role ofheterogeneous factors. Findings advance our understanding of social cognition in brain health anddisease, with implications for predictive models, assessments, and interventions.